MoO3/Ag/MoO3 anode for organic light-emitting diodes and its carrier injection property. (16th April 2015) - Banzai, Kazuki; Naka, Shigeki; Okada, Hiroyuki
Abstract: We report on the application of the dielectric/metal/dielectric (DMD) structure consisting of a molybdenum trioxide (MoO3 )/silver (Ag)/MoO3 stack as the transparent electrode in organic light-emitting diodes (OLEDs). Bright emission similar to that of the indium–tin-oxide anode (ITO) device was obtained from the OLEDs with the DMD anode. Also, the barrier height at the interface of DMD/bis[ N -(1-naphthyl)- N -phenyl] benzidine (α-NPD) is similar to that at the ITO/α-NPD interface. The DMD electrode is a promising anode for OLEDs.